Review of unreported shore-fly genera of the tribe Scatellini from the New Zealand subregion (Diptera: Ephydridae) with description of three new species - Mathis, Wayne N.; Zatwarnicki, Tadeusz; Marris, John W.m. (Zootaxa, 2004)
Two unreported genera and their included species of the shore-fly tribe Scatellini Wirth and Stone that occur in the New Zealand subregion are reviewed. One genus, Haloscatella Mathis, is represented by three species in the subregion and Limnellia Malloch by two. Three of the species, all in the genus Haloscatella, are new (type locality in parenthesis): H. balioptera (New Zealand. Chatham Island: Tennants Lake (43 49.4’S, 176 34’W)), H. karekare (New Zealand. North Island. AK: Karekare (37 00.2’S, 174 28.8’E)), and H. harrisoni (New Zealand. Bounty Islands: Proclamation Island). The fourth and fifth species are in the genus Limnellia: L. abbreviata (Harrison), new combination (originally described in Scatella), was described from specimens collected on Snares Islands, and L. maculipennis Malloch was originally described from a female collected in Sydney, Australia, and is represented by two females from North Island (near Auckland and Hamilton) and a female from South Island (Christchurch). In addition to describing the new species and to facilitate their identification, the tribe and genera are diagnosed, and a key is provided to the known genera of Scatellini from the New Zealand subregion.